COMPENSATORY AND ADAPTIVE REACTIONS OF A SINGLE KIDNEY AFTER CONTRALATERAL NEPHRECTOMY - Monastyrsky, V.M.; Pivtorak, V.I.; Suhodolya, S.A. (World of Medicine and Biology, 2018)
62 patients with a single kidney who had previously undergone nephrectomy for various reasons were examined. It has been established that nephroptosis of a single kidney after nephrectomy is most often observed in women with ectomorphic somatotype. Both women and men often have lowering of the right kidney. At nephroptoce at stage 1 (10 patients) we observed dull pain in the lumbar region from the side of a single kidney, which weakens in the horizontal position of the patient. At the 2nd stage of nephroptosis (16 patients) the pain spread throughout the stomach and on the back area. At the 3rd stage of nephroptosis (10 patients), when the kidney was mobile in the retroperitoneal space, it was easily displaced in a large or small pelvis, the pain became permanent. At this stage, in cases where the omission of the kidney is accompanied by its rotation (6 patients), short-term stinging pain arose more often. Depending on the stage of lowering the kidneys, the nitrogen function of the kidney deteriorates and is the higher blood pressure.